POST-89 MOLDOVA BY ANDRZEJ STASIUK - Monluçon, Anne-Marie (Porównania, 2014)
The text is aimed at showing the way of portraying the mentality and customs of Moldovians after 1989 in Andrzej Stasiuk’s recollection travelogue from his travels to the countries of former USSR entitled Jadąc do Babadag. Stasiuk’s work is interesting to the author because of the ostalgic reactions of Moldovians who are in the process of searching and defining their identities. However, the most important aspect for the author is to obtain evidence of the Polish postcolinial awareness from the work.